THE NEED AND POSSIBILITIES OF EARLY DIAGNOSIS OF ANKYLOSING SPONDYLITIS: COMMENTARIES ON THE PAPER «EARLY DIAGNOSIS OF ANKYLOSING SPONDYLITIS» (No. 4, 2013) AND DISCUSSION IN THE JOURNAL (No. 2, 2014) - Sh. F. Erdes (Научно-практическая ревматология)
The material is a continuation of the discussion initiated in this journal No. 2, 2014 and caused by the paper «Early diagnosis of ankylosing spondylitis» (No. 4, 2013). Opponents' commentaries on the elaboration and modification of classification criteria are successively considered and commented; much attention is given to the problem of terminology.